Aktivitas Port Clearance Pengurusan Dokumen PT. Pelayaran Sumatra Timur Indonesia - Handoyo Widyanto; Ningrum Astriawati; Suyanti Suyanti; Fikri Fikri (PPPM Polimarin, 2023)
A procurement for the smooth arrival and departure of ships (port clearance) must be in accordance with existing procedures so that ships can leave the port and arrive safely at the destination port. The purpose of this study is to determine activities related to the clearance of document management by PT. Pelayaran Sumatra Timur Indonesia. This research is a type of qualitative descriptive research. In the research method, there are two types of data in this study, namely primary data and secondary data. There are 3 methods of obtaining the data needed during the research time including observation methods, interview methods and documentation methods. The results showed that the clearance activity of PT. East Sumatra Indonesia shipping there are several procedures for handling documents on ships, namely, checking shipping orders, checking cargo manifests or loading lists and checking cargo shipping lists or boot notes and other important ship requirements. The document clearance procedure is divided into two, namely clearance in and clearance out. The clearance procedure is the process of obtaining permits for ships that will arrive at the port to related agencies. Clearance out the procedure on PT. East Sumatra Indonesia shipping includes after the ship has finished carrying out activities at the port and will again sail out of the port area, the agent re-requests the ship's departure or clearance.